Relações de trabalho no campo: estudo de caso da Fazenda Alcoléa - Palmeira, Laura Cristina Fernandes (Universidade Federal de São Carlos, 2015)
Throughout history, there have been different types of labor relations in the Brazilian countryside. The mode of production in the colonial period was represented by the slave system, which was exploited the slave labor force, which also entered the process as a merchandise. In the mid-nineteenth century, the settlers begin to replace the slave labor on farms through labor contracts by casual work or partner who became known as the settlement system. After almost a century, these relations would change to the form of wage labor in the countryside. Hiring fly workers to the harvest period represented one way to not pay workers rights provided by the unregistered. Alcolea farm had some workers of these labor relations, because we found reports of fly workers, registered workers and also unregistered. The proposal to work the agrarian question in school enables students to understand this from their reality.
Work relations in the field: case study of Fazenda Alcoléa
Keywords: Relações de trabalho; Fazenda; Questão agrária; Farm; Agrarian question; Labor relations; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA